2024
DOI: 10.1101/2024.01.08.574736
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The spatial landscape of glial pathology and T-cell response in Parkinson’s disease substantia nigra

Kelly Jakubiak,
Fahad Paryani,
Adithya Kannan
et al.

Abstract: Parkinson’s Disease (PD) is a progressive neurodegenerative disease that leads to debilitating movement disorders and often dementia. Recent evidence, including identification of specific peripheral T-cell receptor sequences, indicates the adaptive immune response is associated with disease pathogenesis. However, the properties of T-cells in the brain regions where neurons degenerate are uncharacterized. We have analyzed the identities and interactions of T-cells in PD in post-mortem brain tissue using single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 150 publications
(226 reference statements)
0
2
0
Order By: Relevance
“…Effector CD4+ and CD8+ T cell subtypes that appear to be more abundant in peripheral blood, cerebrospinal fluid and brains of PD patients are now widely being investigated due to their proinflammatory and cytotoxic profiles (Bhatia et al, 2021; Galiano-Landeira et al, 2020; Jakubiak et al, 2024; Kimura et al, 2024; Lindestam Arlehamn et al, 2020; Schröder et al, 2018; Sulzer et al, 2017; Wang et al, 2021; Williams et al, 2024). Previous findings by our group indeed points to the proliferation of autoreactive CD8+ T cells as a prerequisite for driving late CNS-related pathological process via major histocompatibility class I (MHCI)-mediated antigen presentation by dendritic cells in the spleen (Kazanova et al, 2024; Matheoud et al, 2019; Matheoud et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Effector CD4+ and CD8+ T cell subtypes that appear to be more abundant in peripheral blood, cerebrospinal fluid and brains of PD patients are now widely being investigated due to their proinflammatory and cytotoxic profiles (Bhatia et al, 2021; Galiano-Landeira et al, 2020; Jakubiak et al, 2024; Kimura et al, 2024; Lindestam Arlehamn et al, 2020; Schröder et al, 2018; Sulzer et al, 2017; Wang et al, 2021; Williams et al, 2024). Previous findings by our group indeed points to the proliferation of autoreactive CD8+ T cells as a prerequisite for driving late CNS-related pathological process via major histocompatibility class I (MHCI)-mediated antigen presentation by dendritic cells in the spleen (Kazanova et al, 2024; Matheoud et al, 2019; Matheoud et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Post-mortem studies show a significantly greater density of CD8 T cells (Brochard et al, 2009) and higher levels of pro-inflammatory cytokines in the substantia nigra of PD patients’ brain (Mogi, Harada, Kondo, et al, 1994). A recent study using single nuclei sequencing and spatial transcriptomics revealed increased presence of clonally expanded tissue resident memory CD8 T cells in the substantia nigra of PD patients that had altered interaction with endothelial cells and myeloid cells through TCR - MHCI (Jakubiak et al, 2024). Additionally, the relative abundance of peripheral CD8 T cells to the number of CD4+CD25+ T regulatory cells (Tregs) was found to be significantly higher in PD patients (Baba et al, 2005; Thome et al, 2021).…”
Section: Introductionmentioning
confidence: 99%